KERJASAMA SEKOLAH DAN ORANG TUA DALAM PEMBENTUKAN KARAKTER SISWA DI SEKOLAH DASAR - Muhammad Ilham; Marzuki Marzuki; Waode Eti Hardiyanti; Sri Yuliani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2022)
The purpose of this study was to examine the form of cooperation between schools and parents in the formation of student character at SD Negeri 1 Pangi-Pangi and to examine the obstacles to cooperation between schools and parents in forming student character. This type of research is descriptive qualitative. Informants in this study were principals, teachers, parents and children/students. Data collection techniques were carried out by observation, interviews and documentation. The results showed that the form of cooperation between schools and parents in shaping the character of students at SD Negeri 1 Pangi-Pangi, namely 1) visiting teachers at students' homes to obtain data or information about children's behavior at home, providing understanding to parents that in educating the child is a shared responsibility between parents and educators at school, 2) and parental communication with homeroom teachers to build parental involvement in aligning parenting at home with what is obtained at school through teleohone media or parents coming directly to the school. school. Obstacles of cooperation between schools and parents in shaping the character of students at SDN 1 Pangi-Pangi, namely the attitude of parents who do not respond or do not care about the development of their children at school because parents are busy with their work, so they cannot attend meetings or activities carried out by the school. and submit everything to the school. Keywords: Student Character Building, School Cooperation, Elementary School, Parents